IMPLEMENTASI DIKLAT KEPEMIMPINAN TINGKAT IV DALAM MENINGKATKAN KOMPETENSI PESERTA DIKLAT PADA BALAI DIKLAT KEAGAMAAN MAKASSAR - Nelly Nelly; Edi Jusriadi; Ahmad AC (COMPETITIVENESS, 2021)
Education and training are seen as the main instruments for improving the quality of civil servant human resources which include improving knowledge, improving skills and skills, and changing attitudes and behaviors, and correction to performance weaknesses. So that education and training is the most effective policy instrument to achieve the work competencies required by a position in the bureaucracy. Staffing management system, echelon IV structural officials play a very important role in determining when planning the activities of agencies and subordinate leaders and all stakeholders of the implementation of Leadership Training Level IV aimed at equipping participants with the competencies needed to become operational leaders felt there is not enough need for a training. The application of Level IV Leadership Training at the Makassar Religious Training Center Office, the overall temporary observation is not fully in accordance with the principles of concept and theory of leadership. Leadership Training activities bring changes in both behavior and character changes, with the output of results with the construction of teamwork in completing tasks both individually and organizationally in government tasks, thereby improving performance accountability in the Ministry of Religious Affairs. Can improve the quality of service efficiently and measurably Keywords (10 Bold): Implementation, Leadership, Competence